Associação micorízica em espécies arbóreas, atividade microbiana e fertilidade do solo em áreas degradadas de cerrado - Scabora, Márcia Helena [UNESP]; Maltoni, Kátia Luciene [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP] (My University, 2011)
The recuperation of areas used during the construction of the hydroelectric plant, especially in 'borrowed areas', is a difficult and long process since all vegetation and the fertile layer of soil were removed. Interventions in these degraded areas could accelerate the revegetation process. The objective of this research was to evaluate the association of arbuscular mycorrhizal fungi (AMF) in tree species, microbial activity (basal respiration) and fertility of 'cerrado' degraded areas. Soil from two areas, pasture soil and exposed subsoil, were utilized. Organic and mineral fertilization, and liming, were added to the pit for better seedlings' initial growth, where 50 mL of preserved cerrado soil was applied as inoculum of microorganisms. Seedlings of 11 tree species were planted: Anadenanthera falcata (Benth.) Speg ('angico-preto'), Acacia polyphylla D.C. ('monjoleiro'), Stryphnodendron adstringens (Mart.) Coville ('barbatimão'), Dimorphandra mollis Benth ('faveiro'), Hymenaea stigonocarpa Mart. ex Hayne ('jatobá-de-cerrado'), Dipteryx alata Vog. ('baru'), Machaerium acutifolium Vogel ('jacarandá-do-campo'), Schinus terebinthifolia Raddi ('aroeirapimenteira'), Magonia pubescens St. Hil. ('tingui'), Lafoensia pacari St. Hil. ('dedaleira') and Tabebuia aurea (Manso) Benth. & Hook ('ipê-amarelo'). Twelve months later, root samples were colleted at the depth of 0-0.10 m and used for evaluations. The subsoil, as compared to pasture soil, was poor in organic matter and presented less microbial activity. The highest mycorrhizal colonization was seen in the species Acacia polyphylla D.C. (monjoleiro), Magonia pubescens St. Hil. (tingui), Hymenaea stigonocarpa Mart. ex Hayne (jatobá-de-cerrado) and Schinus terebinthifolia Raddi (aroeira-pimenteira). These species could be indicated in revegetation projects in 'cerrado' degraded areas. Plants from both areas showed seedlings form high mycorrhizal colonization and low numbers of spores.
Mycorrhizal association in tree species, microbial activity and soil fertility on cerrado degraded areas
Keywords: Borrowed area; Evoluted C-CO 2; Revegetation; Subsoil